THE TEACHING OF ENGLISH ORAL COMMUNICATION IN THE APPLICATION OF CURRICULUM 2013 - Syenja Aradhanawaty; Alauddin Madjid (Institut Agama Islam Negeri (IAIN) Kendari, 2016)
This study was meant to (1) understand the teachers’ and students’ perceptions, (2) describe the teachers and students difficulties, and (3) investigate the classroom management and interactions. The subjects, decided purposefully, were three English teachers and approximately 120 students. The data were gathered through classroom observation and in depth interview and analysed by using the interactive model of qualitative data analysis based on Miles and Huberman (1994). The research findings show that both teachers and students positively perceive the development of oral communication through Scientific Approach to teaching and its integrated skills lesson along with the language elements. The teachers find it difficult to develop English oral communication in two features, i.e. overcrowded classroom and students’ lack of active vocabulary. The students, on the other hand, find it hard to learn English oral communication in three characteristics, i.e. psychological-based problem, language use-based problem, and environmental-based problem. The classroom management and interaction support the students’ improvement in their speaking ability under communicative task and activity. The study recommended for further close inquiry into the functions of skill getting and skill using activity and their contributions to increase communicative language acquisition.